THE IMPACT OF ISLAMIC CORPORATE GOVERNANCE DISCLOSURE, ISLAMIC INTELLECTUAL CAPITAL, ZAKAT, FINANCIAL PERFORMANCE (SCnP Model) & ISLAMIC ETHICAL IDENTITY TO SUSTAINABLE BUSINESS - Yulinda Putri Prativi; Citra Sukmadilaga; Cupian Cupian (Universitas Airlangga, 2021)
ABSTRAKTujuan dari penelitian ini adalah untuk menganalisis dampak Islamic Corporate Governance disclosure, Islamic Intellectual Capital, Zakat, Kinerja Keuangan (SCnP Model), dan Islamic Ethical Identity terhadap Sustainable Business. Penelitian ini menggunakan pendekatan kuantitatif. Data yang dipakai ialah data sekunder dengan teknik pengumpulan data content analysis terhadap annual report 5 bank syariah periode 2015-2019 yang terdapat di negara ASEAN, GCC & MESA. Metode analisis data pada penelitian ini menggunakan regresi linier berganda. Hasil penelitian menunjukkan bahwa (1) Islamic Corporate Disclosure berpengaruh terhadap Sustainable Business, (2) Islamic Intellectual Capital berpengaruh terhadap Sustainable Business, (3) Zakat tidak berpengaruh terhadap Sustainable Business, (4) Kinerja Keuangan (SCnP Model) tidak berpengaruh terhadap Sustainable Business, (5) Islamic Ethical Identity tidak berpengaruh terhadap Sustainable Business. Penelitian ini diharapkan dapat memberikan masukan bagi entitas syariah terutama bank syariah dalam pengembangan aspek kinerja keuangan dan non keuangan serta mengi ngatkan kembali akan pentingnya konsep sustainable terutama kewajiban dalam penyusunan sustainability reporting.Kata Kunci: Islamic Corporate Governance, Islamic Intellectual Capital, Zakat, Islamic Ethical Identity, Sustainable Business. ABSTRACTThe purpose of this study is to analyze the impact of Islamic Corporate Governance disclosure, Islamic Intellectual Capital, Zakat, Financial Performance (SCnP Model), and Islamic Ethical Identity on Sustainable Business. This study uses a quantitative approach. The data used is secondary data with content analysis data collection techniques on the annual reports of 5 Islamic banks for the 2015-2019 period in ASEAN, GCC & MESA countries. Methods of data analysis in this study using multiple linear regression. The results showed that (1) Islamic Corporate Disclosure has an affects to Sustainable Business, (2) Islamic Intellectual Capital has an effect on Sustainable Business, (3) Zakat has no effect on Sustainable Business, (4) Financial Performance (SCnP Model) has no effect on Sustainable Business , (5) Islamic Ethical Identity has no effect on Sustainable Business. This research is expected to provide input for Islamic entities, especially Islamic banks in developing aspects of financial and non-financial performance as well as reminders of the importance of the concept of sustainability, especially the obligations in preparing sustainability reporting.Keyword: Islamic Corporate Governance, Islamic Intellectual Capital, Zakat, Islamic Ethical Identity, Sustainable Business.REFERENCESAkhtar, C. S., Ismail, K., Ndaliman, M. A., Hussain, J., & Haider, M. (2015), Can intellectual capital of smes help in their sustainability efforts. Journal of Management Research, 7(2), 83-97.Akisik, O., & Gal, G. (2011). Sustainability in businesses, corporate social responsibility, and accounting standards: An empirical study. International Journal of Accounting and Information Management, 19(3), 304–324.Alam, N. (2010). Islamic venture philanthropy: A tool for sustainable community development. SSRN Electronic Journal, (March), 1-14. https://dx.doi.org/10.2139/ssrn.1565859Al-Qardhawi, Y. (2000). Bagaimana berinteraksi dengan Al-Qur'an. Jakarta: Pustaka Al-Kautsar.Anam, M. K. (2017). Penerapan PSAK 101 pada laporan dana zakat dan dana kebajikan. Misykat Al Anwar, 28(2), 1-14. https://doi.org/10.31904/ma.v28i2.3838Apriliya, N. L., & Maslichah, M. (2019). Analisis kinerja perbankan syariah dengan pendekatan maqashid index dan sharia conformity and profitability (SCnP). Jurnal Ilmiah Riset Akuntansi, 8(3), 11-20.Aydin, Necati. (2013). Islamic social business for sustainable development and subjective wellbeing. International Journal of Islamic and Middle Eastern Finance and Management, 8(4), 491–507.Berrone, P., Surroca, J., & Tribó, J. A. (2007). Corporate ethical identity as a determinant of firm performance: A test of the mediating role of stakeholder satisfaction. Journal of Business Ethics 76(1), 35-53.Chapra, M. U., & Ahmed, H. (2002). Corporate governance in Islamic financial institutions. Jeddah: Islamic Development Bank.Choudhury, M.A., & Hoque, M. Z. (2006). Corporate governance in Islamic perspective. Corporate Governance, 6(2), 116-128.Elkington, J. (1998). Accounting for the triple bottom line. Measuring Business Excellence, 2(3), 18-22. https://doi.org/10.1108/eb025539Erol, C., F. Baklaci, H., Aydoğan, B., & Tunç, G. (2014). Performance comparison of Islamic (participation) banks and commercial banks in Turkish banking sector. Euromed Journal of Business, 9(2), 114-128.Firer, S., & Williams, S. M. (2003). Intellectual capital and traditional measures of corporate performance. Journal of intellectual capital, 4(3), 348-360.Ghozali, I. (2018). Aplikasi analisis multivariate dengan program SPSS 25. Semarang: Badan Penerbit Universitas Diponegoro.Haniffa, R., & Hudaib, M. (2007). Exploring the ethical identity of Islamic Banks via communication in annual reports. Journal of Business Ethics, 76(1), 97–116.Hasan, Z. (2011). A survey on Shariah governance practices in Malaysia, GCC countries and the UK: Critical appraisal. International Journal of Islamic and Middle Eastern Finance and Management, 4(1), 30-51.Hasan, Z. (2011). Shariah governance in Islamic financial institutions in Malaysia, GCC countries, and the UK. Durham Theses. Durham: Durham University.Hassan, A., & Chachi, A. (2005). The role of Islamic financial institutions in sustainable development. Islamic Finance and Economic Development, 59–93.Iqbal, Z., & Mirakhor, A. (2004). Stakeholders model of governance in Islamic economic system. Islamic Economic Studies, 11(2), 44-63Kubo, I., & Saka, A. (2002). An inquiry into the motivations of knowledge workers in the Japanese financial industry. Journal of Knowledge Management, 6(3), 262-271. https://doi.org/10.1108/13673270210434368Kuppusamy, M., Saleh, A. S., & Samudhram, A. (2010). Measurement of Islamic banks performance using a shariah conformity and profitability model. Review of Islamic Economics, 13(2), 35–48.Majid, N. A., Sulaiman, M., & Ariffin, N. M. (2011). Developing a corporate governance disclosure index for Islamic financial institutions. 8th International Conference on Islamic Economics and Finance, 1-25.Mutia, E., & Musfirah, N. (2017). Pendekatan maqashid shariah index sebagai pengukuran kinerja perbankan syariah di Asia Tenggara. Jurnal Akuntansi dan Keuangan Indonesia, 14(2), 181–201.Nawaz, T., & Haniffa, R. (2017). Determinants of financial performance of Islamic banks: an intellectual capital perspective. Journal of Islamic Accounting and Business Research, 8(2), 130-142. https://doi.org/10.1108/JIABR-06-2016-0071Prasetyowati, L. A., & Handoko, L. H. (2019). Pengukuran kinerja bank umum syariah dengan maqasid index dan sharia conformity and profitability (SCnP). Jurnal Akuntansi dan Keuangan Islam, 4(2), 107–130.Rahma, Y. (2018). The effect of intellectual capital and islamic performance index on financial performance. Jurnal Ilmu Akuntansi, 11(1), 105-116.Ramadhan, M. I. B., Abdurahim, A., & Sofyani, H. (2018). Modal intelektual dan kinerja maqashid syariah perbankan syariah di Indonesia. Jurnal Akuntansi dan Keuangan Islam, 6(1), 5-18.Rashid, M., & Hassan, M. K. (2014). Market values of Islamic banks and ethical identity. American Journal of Islamic Social Sciences, 31(2), 43-79. https://doi.org/10.35632/ajiss.v31i2.289Ratnaputri, W. (2013). The analysis of islamic bank financial performance by using camel, shariah conformity and profitability (SCnP). Jurnal Dinamika Manajemen, 4(2), 215-226.Sarea, A. M. (2013). Accounting treatment of zakah: Additional evidence from AAOIFI. Journal of Islamic Banking and Finance, 1(1), 23–28Sari, M. P. Y., & Marsono, M. (2013). Pengaruh kinerja keuangan, ukuran perusahaan dan corporate governance terhadap pengungkapan sustainability report. Diponegoro Journal of Accounting, 2(3), 580–589.Siswanti, I., Salim, U., Sukoharsono, G., & Aisjah, S. (2017). The impact of Islamic corporate governance, Islamic intellectual capital and Islamic financial performance on sustainable business Islamic banks. International Journal of Economics and Financial Issues, 7(4), 316–323.Suryasnia, S., Primiana, I., Sucherly., & Herwany, A. (2020). Banking strategy and implementation of banking ASEAN integration framework (ABIF) in ASEAN community (AEC)’s era 2020 ERA 2020. Munich Personal Repec Archive Banking, 73303.Triyuwono, I. (2009). Perspektif, metodologi, dan teori akuntansi syariah. Jakarta: Rajawali Press.Ullman, A. (1985). Data in search of a theory: A critical examination of the relationship among social performance, social disclosure and economic performance. Academy of Management Review, 10(3), 540-577.Ulum, I. (2013). Model pengukuran kinerja intellectual capital dengan IB-VAIC di perbankan Syariah. Inferensi, 7(1), 185-206.Ulum, I., Ghozali, I., & Chariri, A. (2008). Intellectual capital dan kinerja keuangan perusahaan; Suatu analisis dengan pendekatan Partial Least Squares (PLS), 1-31.Wahab, N. A., & Rahman, A. R. A. (2011). A framework to analyse the efficiency and governance of zakat institutions. Journal of Islamic Accounting and Business Research, 2(1), 43-62. https://doi.org/10.1108/17590811111129508Widhiani, B. R. (2018). Pengaruh kinerja bank syariah dengan pendekatan sharia conformity and profitability model dan dampaknya terhadap kepercayaan stakeholder. Akurasi: Jurnal Studi Akuntansi dan Keuangan, 1(2), 137–148.Yunus, M. (2014). The seven principles of social business. Diakses dari www.grameencreativelab. com/a-concept-to-eradicate-poverty/7-principles.html